Sacred and Profane in Chaucer and Late Medieval Literature Essays in Honour of John V. Fleming - Epstein, Robert (University of Toronto Press, 2016)
Literary depictions of the sacred and the secular from the Middle Ages are representative of the era's widely held cultural understandings related to religion and the nature of lived experience. Using late Medieval English literature, including some of Chaucer's writings, these essays do not try to define a secular realm distinct and separate from the divine or religious, but instead analyze intersections of the sacred and the profane, suggesting that these two categories are mutually constitutive rather than antithetical.With essays by former students of John V. Fleming, the collection pays tribute to the Princeton University professor emeritus through wide-ranging scholarship and literary criticism. Including reflections on depictions of Bathsheba, Troilus and Criseyde, the Legend of Good Women, Chaucer's Pardoner, and Margery Kempe, these essays focus on literature while ranging into history, philosophy, and the visual arts. Taken together, the work suggests that the domain of the sacred, as perceived in the Middle Ages, can variously be seen as having a hierarchical or a complementary relationship to the things of this world
Description based on online resource; title from PDF title page (publisher's Web site, viewed June 01., 2017)
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Holy, The, in literature; Secularism in literature